Effect of seed mass and number of cotyledons on seed germination after heat treatment in Pinus sylvestris L. var. iberica Svob. - Castoldi, Elena; Molina, Jose A. (Forest Systems, 2014)
Aim of study: We investigated the combined effect of seed mass and number of cotyledons on the seed germination of Pinus sylvestris var. iberica (Iberian Scots pine) in simulated fire conditions. Material and Methods: We used 3,600 fresh seeds extracted from 158 cones obtained from 10 pine trees located at the Biological Station of the Complutense University (Guadarrama mountains, Madrid region). All the seeds were individually weighed and assigned to one of the two following seed mass classes: class I (1.6-12.5 mg) and class II (12.6-145.0 mg). Germination capacity (GC) and mean germination time (MGT) were studied in combined experiments of four different temperatures (100°, 125°, 150° and 175°C) and two exposure times (1 and 5 minutes) together with a control (no treatment). Four replicates of 50 seeds each were used for each treatment and hydrated daily for 14 days to germinate under constant illumination. The number of cotyledons was counted in seedlings. Main results: Germination was depressed at above 125°C for 5 min. GC and MGT were negatively related, and were influenced by temperature and exposure time. Seed mass was found to have a significant effect on GC at some moderate heat treatment but not on MGT. The number of cotyledons was positively correlated to seed mass but there was not found correlated with germination after seed heat treatments. Research highlights: In the case of the Iberian Scots pine, higher seed mass mitigate the negative effects of temperature on seed germination after moderate heat treatment simulating fire. Keywords: Fire disturbance; germination; Mediterranean mountains; Pinus sylvestris L. var. Iberica; temperature.